Investigation on the performance of solar kiln for wood drying in different seasons in Karaj - asghar tarmian (Regional Information Center for Science and Technology (RICeST), 2016)
In this research, the performance of a semi-greenhouse solar kiln was evaluated for dying different wood species in different season in Karaj. This study was carried out in two separate parts. In the first part, the flat-sawn boards of oak and fir with a nominal thickness of 50 mm were dried during summer of the year 2012. In the second part, the flat-sawn boards of beech and poplar with the same thickness were dried in autumn, 2014 and spring, 2015. For both parts, the boards were also air-dried. The temperature measured inside the solar kiln was 35 ºC greater than that outside during daytime and also the kiln temperature ranged from 55 to 75ºC during 10 a.m. to 2 p.m.. In both parts of research, all wood species dried in the solar kiln faster with better quality compared to those air-dried. The severity of casehardening and surface checking in the boards dried in the solar kiln was lower and more homogenous moisture profile was observed. In addition, the final moisture content was lower for the boards dried in the solar kiln.